The cowboy's Easter surprise - Kemerer, Jill (Kemerer, Jill. Wyoming legacies, 2025)
"As temporary guardian of his three nieces, stable manager Trent Lloyd is in desperate need of a babysitter. His only option: former classmate Gracie French, who's back in town and determined to prove she's a responsible, independent adult. The girls instantly adore Gracie, and after a fun-packed Easter weekend, Trent fears he's not the only one captivated by Gracie's charm. But he can't forget the wild child he knew in high school. If he can trust Gracie with his nieces, can he also learn to trust her with his heart?" --